(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the one of the most interesting problems in the history of Ukraine (the 20th of XX century). It analyzes impediments on the way of ukrainization and positive factors that made its development easy. The author proves that there was an objective necessary of ukrainization for a Ukrainian society of that time.